Innovation, engagement and development: moving forward in health information settings. (8th June 2018) - Spring, Hannah
Abstract: The current trends influencing change in health information and library settings are presenting some exciting new opportunities for health information specialists. Increasingly, knowledge specialists are playing a pivotal role in the effective mobilisation of knowledge and evidence. The focus for our profession will continue to be on demonstrating the value and impact of our services, but a shift in expectations about how those services are delivered will need to be underpinned by new tools and skill sets. These issues are reflected in the themes of the Health Libraries Group 2018 conference, and in conjunction with the event, this virtual issue draws together a collection of articles reflecting those themes. Topics covered in the virtual issue include the following: Toolkits, online systems and emergent technologies to support health information practice; Continuing professional development; Community projects, engagement, outreach and public health; Value and impact and evidence‐based practice; Service improvement and library management; and Digital and health literacy. The papers selected for this issue provide some excellent examples of how we, as a profession, are initiating change in creative ways and rising to the exciting challenges of the future.